2024
DOI: 10.1021/acsami.3c13075
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring of Visible to Near-Infrared Active 2D MXene with Defect-Enriched Titania-Based Heterojunction Photocatalyst for Green H2 Generation

Sudeshna Das Chakraborty,
Uttam Kumar,
Pallab Bhattacharya
et al.

Abstract: A wide solar light absorption window and its utilization, long-term stability, and improved interfacial charge transfer are the keys to scalable and superior solar photocatalytic performance. Based on this objective, a noble metal-free composite photocatalyst is developed with conducting MXene (Ti 3 C 2 ) and semiconducting cauliflower-shaped CdS and porous Cu 2 O. XPS, HRTEM, and ESR analyses of TiO y @Ti 3 C 2 confirm the formation of enough defect-enriched TiO y (where y is < 2) on the surface of Ti 3 C 2 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…MXenes with the M n +1 X n T x formula (M: early transition metal, X: C and/or N, T x : functional groups, n = 1–4) are two-dimensional (2D) multilayered materials that recently emerged as cocatalysts for photocatalytic applications due to their unique structural and electronic properties. , As photocatalysts, the formed MXene-derived transition metal oxides (MO x ) can be highly efficient nanomaterials for photocatalytic applications. , MXene-derived MO x are obtained by partial or complete oxidation of MXene (Ti 3 C 2 T x and Ti 2 CT x ) depending on oxidation conditions, and they exhibit superior properties compared to MO x /MXene composites. , Recent advancements in MXene-based photocatalysts highlight their growing significance in environmental and energy challenges, and ongoing research aims to overcome the current limitations and scale up their production for practical applications. Reported studies pointed out that oxygen-containing functional groups, especially, facilitate the formation of MO x phases . It has been reported that TiO 2 /amorphous carbon sheets can be derived by using flash-heating multilayered Ti 3 C 2 T x in air .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…MXenes with the M n +1 X n T x formula (M: early transition metal, X: C and/or N, T x : functional groups, n = 1–4) are two-dimensional (2D) multilayered materials that recently emerged as cocatalysts for photocatalytic applications due to their unique structural and electronic properties. , As photocatalysts, the formed MXene-derived transition metal oxides (MO x ) can be highly efficient nanomaterials for photocatalytic applications. , MXene-derived MO x are obtained by partial or complete oxidation of MXene (Ti 3 C 2 T x and Ti 2 CT x ) depending on oxidation conditions, and they exhibit superior properties compared to MO x /MXene composites. , Recent advancements in MXene-based photocatalysts highlight their growing significance in environmental and energy challenges, and ongoing research aims to overcome the current limitations and scale up their production for practical applications. Reported studies pointed out that oxygen-containing functional groups, especially, facilitate the formation of MO x phases . It has been reported that TiO 2 /amorphous carbon sheets can be derived by using flash-heating multilayered Ti 3 C 2 T x in air .…”
Section: Introductionmentioning
confidence: 99%
“… 18 , 19 As photocatalysts, the formed MXene-derived transition metal oxides (MO x ) can be highly efficient nanomaterials for photocatalytic applications. 20 , 21 MXene-derived MO x are obtained by partial or complete oxidation of MXene (Ti 3 C 2 T x and Ti 2 CT x ) depending on oxidation conditions, and they exhibit superior properties compared to MO x /MXene composites. 22 , 23 Recent advancements in MXene-based photocatalysts highlight their growing significance in environmental and energy challenges, and ongoing research aims to overcome the current limitations and scale up their production for practical applications.…”
Section: Introductionmentioning
confidence: 99%
“…Hydrogen generation through photocatalytic water splitting is an environmentally friendly strategy. It offers potential solutions to both the energy crisis and environmental challenges. Photocatalysts have an important effect on light absorption efficiency and photocatalytic activity. A typical photocatalytic process involves four consecutive steps .…”
mentioning
confidence: 99%